From Concept to Practice: Ijtihad Jama’i as a Method for Issuing Halal Product Fatwa from the Perspective of Kiai in Bangkalan, Madura - Holis, Holis; Musadad, Ahmad; Setiawan, Firman; Pujiati, Tri (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study aims to analyze the perspectives of Madurese scholars on the application of collective ijtihad (ijtihad jama’i) as a method for determining halal product fatwas. This method is viewed as an effective solution to address the complexity of contemporary issues that cannot be resolved individually. Employing a descriptive qualitative approach, the study collected data through in-depth interviews with scholars from Bangkalan, such as Kiai Ma’ruf Khozin and Kiai Nur Hasyim, complemented by observation and documentation techniques. The findings reveal that Madurese scholars strongly support the implementation of collective ijtihad in halal product fatwa issuance, as it enhances the accuracy of rulings, reinforces their legitimacy, and preserves the values of maq??id al-shar?‘ah. Nevertheless, several challenges were identified, including limited access to contemporary references and the need to strengthen scholarly capacity. The study recommends optimizing the role of bahtsul masail forums, enhancing collaboration among scholars, academics, and halal certification institutions, and expanding the practice of collective ijtihad to the district level. These findings are expected to contribute significantly to strengthening collective-based halal fatwa determination methods amidst the growing demands of the halal industry in Indonesia   [Penelitian ini bertujuan untuk menganalisis pandangan ulama Madura terhadap penggunaan ijtihad jama’i sebagai metode penetapan fatwa produk halal. Metode ini dipandang sebagai solusi efektif dalam menghadapi kompleksitas persoalan kontemporer yang tidak dapat diselesaikan secara individu. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik wawancara mendalam terhadap para ulama Bangkalan, seperti Kiai Ma’ruf Khozin dan Kiai Nur Hasyim, serta dilengkapi observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa ulama Madura sangat mendukung penerapan ijtihad jama’i dalam penetapan fatwa produk halal, karena mampu meningkatkan akurasi, memperkuat legitimasi fatwa, dan menjaga nilai-nilai maq??id syar?‘ah. Namun, beberapa tantangan turut diidentifikasi, seperti keterbatasan akses terhadap literatur kontemporer dan perlunya penguatan kapasitas keilmuan ulama. Penelitian ini merekomendasikan optimalisasi forum bahtsul masail, penguatan sinergi antarulama, akademisi, dan lembaga sertifikasi halal, serta perluasan penerapan ijtihad jama’i hingga tingkat kabupaten. Temuan ini diharapkan dapat menjadi kontribusi penting dalam memperkuat metode penetapan fatwa halal berbasis kolektif di tengah dinamika kebutuhan industri halal di Indonesia]